Strategi Peningkatan Usaha Ikan Asin Melalui Pelatihan Digital Marketing di Pengasinan Muara Angke - Yani, Ari Soeti; Lukiyana, Lukiyana; Fauzi, Yoga (Jurnal Pemberdayaan Nusantara, 2024)
Participants are asked to understand easy strategies for promoting social media products. Speakers also discussed the value of customer reviews in their marketing plans for the goods they provide. The training participants looked enthusiastic about the content presented by the presenters. The training participants were also made aware of the shortcomings of digital marketing, namely that it cannot be done instantly and requires a lot of experience. Therefore, as a businessman you still have to learn how to use digital marketing gradually. The need for continuous and consistent learning is very necessary to continue to meet the public's sales targets. The evaluation of this activity considers the progress of the training results and the participants' experience when practicing using digital marketing. In general, the participants expressed praise and were happy with the progress of this digital marketing training perfectly. Because all participants have cellphones with digital marketing capabilities, there are no significant obstacles in realizing this community service activity.